Development And Validation Of Learning Resource Materials In Upgrading Comprehension Skills Of Senior High School Students - Morelos, Reinel Lazaro (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This study sought to develop and evaluate learning resource material in upgrading reading comprehension skills of Grade 11 to meet the pressing need of Doňa Candelaria Meneses Duque National High School. The researcher utilized the descriptive survey method which uses questionnaires as the primary tools in gathering desired data information. There were two sets of questionnaire which were used in the study. The first questionnaire is the Reading Diagnostic Test while the second research instrument is the evaluation tool for the developed learning resource materials. The subjects of this study are in two groups: one hundred twenty three (123) randomly selected Grade 11 senior high school students at Doña Candelaria Meneses Duque National High School (DCMDNHS) at Bulakan, Bulacan during the school year 2017-2018; and five ESL teachers, who evaluated the resource materials. The data collected were encoded and entered into the matrix using the computer software of Microsoft Excel with the following statistical procedures: frequency distribution, percentage score, mean, total mean and standard deviation. Based on the results of the diagnostic test, the researcher developed the learning resource materials, and these were validated by five ESL teachers using a 5- point Likert Scale in terms of the following criteria: objectives, contents, vocabulary, usefulness and presentation. Generally, after the evaluation, the overall mean gained of the instructional materials is 4.72, interpreted as “Excellent”. This computed overall mean attests and suggests that the developed learning resource materials in reading are acceptable. The study recommends that the language teachers need to provide the students the means towards maximum growth in accordance with their reading ability. The teachers must help students acquire basic comprehension skills and strategies in sequential reading program designed to reinforce the skills and appreciation of previous skills acquired and to develop new skills that are needed. Likewise, it is also suggested that the administrators should conduct or sponsor programs and in-service trainings to ensure the necessary updated innovations on the preparation and development of instructional materials, particularly in reading comprehension skills. Further, future researchers should conduct a research-driven strategy that can improve the reading comprehension skills of the students